Is the carnage on our roads justified? (2006)
The magnitude of carnage 01! Nigerian roads has become worrisome in recent times. Over the years, the number of people who have lost their lives in road accidents has been on the increase. For example, between 1960 and 2001, over 250,000 fatalities were recorded. Specifically in 1960, 1,083 people died through road traffic accidents. This figure jumped to 8,102 deaths in 2001, an increase of more than 600%. This could be described as a national "calamity". Human error accounted for more than 80% of the cases. In the same vein, the pattern of fatality in some selected states in Nigeria between 1996-2000 showed that Lagos state all the average was responsible for more than 8% of the total road accident fatality in the country during the period of analysis. Whereas in terms of fatality rate and severity index, Lagos state came second and last respectively. Urgent and proactive steps are therefore needed to step down the level of carnage on Nigerian roads. Both the Nigerian Police and the Federal Road Safety commission (FRSC) should be reorganized and overhauled while health institution's should be strengthened Government should as a matter of urgency establish Road Safety Research Institute charged with the sole responsibility of conducting research on safety measures.